One-pot synthesis of 2,4,5-trisubstituted imidazoles using MoO3/SiO2, an efficient and recyclable catalyst - Bhosale, Sidhanath V.; Kalyankar, Mohan B.; Nalage, Santosh V.; Bhosale, Dattatry S.; Pandhare, Swati L.; Kotbagi, Trupti V.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Synthetic Communications, 2011)
[image omitted] A simple one-pot synthesis has been developed for the synthesis of 2,4,5-trisubstituted imidazoles using an efficient and recyclable MoO3/SiO2 solid acid catalyst by condensation of benzil or benzoin, benzaldehyde, and ammonium acetate in acetonitrile as a solvent. Using this solid catalyst, the reactions could be carried out under mild reaction conditions with very good yield of imidazoles, up to 95%. This catalyst could be recycled very easily, which makes this methodology environmentally benign.
Keywords: benzil; benzoin; cyclocondensation; imidazoles; MoO3; One-pot; SiO2; solid acid

One-pot sol-gel preparation for efficient cobalt-molybdenum-titania hydrotreating catalysts - Nguyen, D. L.; Gillot, S.; Souza, D. O.; Blanchard, P.; Lamonier, Carole; Berrier, E.; Kotbagi, T. V.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Cristol, S.; Payen, E.; Lancelot, Christine (Chemcatchem, 2012)
Titania-based hydrodesulfurization catalysts were prepared by using a one-pot solgel method with the titanium peroxo complex as titanium precursor and molybdenum and cobalt precursors dissolved in the aqueous hydrogen peroxide solution used during synthesis. Catalysts with MoO3 loadings varying from 5 to 40 wt?% and a Co/Mo atomic ratio of 0.5 were prepared. Solids with molybdenum loadings below 20 wt?% MoO3 demonstrated poor hydrodesulfurization activity for the model compound thiophene. This was attributed to the presence of a large amount of embedded cobalt and molybdenum species in the titania matrix. A significant increase in the catalytic activity was observed for solids containing 20 and 25 wt?% of MoO3 on which active species appeared to be accessible on the titania surface. Furthermore, the highest conversion obtained on these solgel solids was superior to the highest conversion obtained on reference catalysts prepared through the impregnation of ammonium heptamolybdate and cobalt nitrate on commercial titania.
Keywords: cobalt; heterogeneous catalysis; Molybdenum; sol-gel process; titanium

One-pot synthesis of ultrasmall MoO3 nanoparticles supported on SiO2, TiO2, and ZrO2 nanospheres: an efficient epoxidation catalyst - Chandra, Prakash; Doke, Dhananjay S.; Shubhangi B. Umbarkar; Biradar, Ankush V. (Journal of Materials Chemistry A, 2014)
Ultrasmall molybdenum oxide (MoO3) nanoparticles supported on various (SiO2, TiO2 or ZrO2) nanospheres were synthesized in one pot using a reverse micelle method. The prepared catalysts were thoroughly characterized by various physico-chemical methods. TEM images showed uniform dispersion of MoO3 nanoparticles (1.5-4 nm) onto silica (similar to 275 nm). No separate MoO3 particles were identified from TEM for MoO3/TiO2 (similar to 10.5 nm) and MoO3/ZrO2 (similar to 6.5 nm) because AHM reacted with titanium and zirconium hydroxides to form solid solution. Among the prepared catalysts MoO3/SiO2 showed excellent catalytic activity (up to 90% conversion and 100% epoxide selectivity) for olefin epoxidation. The catalyst was successfully recycled up to five cycles without losing much activity and selectivity.